Time-Resolved Measurement of the ATP-Dependent Motion of the Group II Chaperonin by Diffracted Electron Tracking - Ogawa, Naoki (Int J Mol Sci, 2018)
Previously, we demonstrated the ATP-dependent dynamics of a group II chaperonin at the single-molecule level by diffracted X-ray tracking (DXT). The disadvantage of DXT is that it requires a strong X-ray source and also perfect gold nano-crystals. To resolve this problem, we developed diffracted electron tracking (DET). Electron beams have scattering cross-sections that are approximately 1000 times larger than those of X-rays. Thus, DET enables us to perform super-accurate measurements of the time-resolved 3D motion of proteins labeled with commercially available gold nanorods using a scanning electron microscope. In this study, we compared DXT and DET using the group II chaperonin from Methanococcus maripaludis (MmCpn) as a model protein. In DET, the samples are prepared in an environmental cell (EC). To reduce the electron beam-induced protein damage, we immobilized MmCpn on the bottom of the EC to expose gold nanorods close to the carbon thin film. The sample setup worked well, and the motions of gold nanorods were clearly traced. Compared with the results of DXT, the mobility in DET was significantly higher, which is probably due to the difference in the method for immobilization. In DET, MmCpn was immobilized on a film of triacetyl cellulose. Whereas proteins are directly attached on the surface of solid support in DXT. Therefore, MmCpn could move relatively freely in DET. DET will be a state-of-the-art technology for analyzing protein dynamics.